FAKTOR SUKSES PENERBITAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KABUPATEN GIANYAR BALI - Nyoman Martha Jaya; G.A.P. Candra Dharmayanti; Ida Ayu Cri Vinantya Laksmi (JURNAL SPEKTRAN, 2019)
THE SUCCESS FACTORS IN THE ISSUANCE OF BUILDING PERMIT (IMB) IN GIANYAR REGENCY, BALIABSTRACTThe improvement of development sector in Gianyar Regency has increased every year. This leads to the increasing of the number of the registration of Building Permit (IMB). Normally, IMB registration process takes 7 working days.. In fact this process can take longer than 7 working days, therefore disappointing to the applicants. The number of complaints that arise as well as the occurrence of cases of illegal levies in the permit service IMB caused the accountability of the service and the level of satisfaction of the applicants were questioned. Based on this situation, there is a need to analize the factors that influence the accountability and the level of satisfaction of the applicant. This research used a mixed methodinvolved survey and interview using a questionnaire. The respondents were selected based on nonprobability sampling technique (purposive sampling), covered the respondent which completed all stages of IMB’s registration process, ranging from the consultation stage to the issue of the permits in 2017. Analysis was performed using Analytical Hierarchy Process (AHP) method by assessing the importance level among alternatives under certain criteria, to obtain the weight of each alternative. The results showed that several important factors that influence on the evaluation of accountability of IMB service and the satisfaction of the applicant included timeliness (14,6%), accuracy and honesty (12,8%), responsible and non-discriminative (12,8%), and accuracies of staff (12.6%). Meanwhile, the important factors related on the evaluation of the applicant's satisfaction were timeliness (15.0%), responsible and non-discriminatory factor (13.3%), retribution cost factor (12.7%).